RELATION OF TOTAL CHOLESTEROL TO PROSTATE VOLUME AND INTRAVESICAL PROSTATIC PROTRUSION IN BENIGN PROSTATIC HYPERPLASIA PATIENTS - Made Devi Desyana Arisandi; Wahyudi, Septa Surya; Fatmawati, Heni (Indonesian Journal of Urology, 2021)
Objective: To determine the relationship between total cholesterol, prostate volume, and intravesical prostatic protrusion in patients with benign prostatic hyperplasia. Material & Methods: This study used a cross-sectional method, carried out at the Paru and Bina Sehat Hospital in Jember. The sample in this study was BPH patients who met the inclusion criteria taken through medical record data from October 2019 to January 2020 Results: Samples on this study amounted to 33 patients. In this study, there was a difference between normal and high cholesterol with prostate volume in BPH patients (p = 0.00) and there was a significant relationship between cholesterol and prostate volume with strong correlation strength (p = 0.00 and r = 0.751) while the difference between high and normal cholesterol with IPP obtained insignificant results (p = 0.211) and the correlation between cholesterol and IPP obtained an insignificant relation with weak correlation strength (p = 0.217 and r = 0.221). Conclusion: There is a significant relationship between total cholesterol and prostate volume and a significant difference in prostate volume between normal and high total cholesterol in BPH patients, while there is no significant result between total cholesterol and intravesical prostatic protrusion in BPH patients.